Prevalence and species diversity of nontuberculous mycobacteria in drinking water supply system of Bahía Blanca City, Argentina - Oriani, Alejandra Soledad; Marfil, Maria Jimena; Zumarraga, Martin Jose; Baldini, Mónica Diana (Wolters Kluwer; Asian African Society of Mycobacteriology, 2019)
Background: There is evidence that tap water is the vehicle through which nontuberculous mycobacteria (NTM) infect or colonize the human body. The objective of this study was to determine the presence and diversity of NTM in the water distribution system of Bahía Blanca city, Argentina (sites S2/S3) and in the dike that supplies water to it (S1). Methods: Culture-dependent method, biochemical tests, and molecular method (16S rRNA sequencing gene) were combined to detect and identify NTM. Results: NTM were isolated in 51.6% (64/124) of all the samples analyzed. Mycobacterium gordonae was the most frequently isolated organism (15/64) in all samples analyzed, followed by Mycobacterium peregrinum and Mycobacterium frederiksbergense. Significant differences were found in the residual chlorine values between sampling S2 and S3. In both sites, maximum counts were recorded but they did not correlate with low chlorine values. A concentration higher than 500 colony-forming unit/L of NTM was never found, which can be attributed to the negative effect caused by decontamination methods being a point to consider for the recovery of NTM. In 46.9% (30/64) of samples, both methods coincided in the identification, and the obtained sequences presented ≥99% identity. Identification at the species level was achieved in 50% (32/64) of the isolates. Nearly 17.2% (11/64) of the isolates showed a similarity <99%. Conclusions: It should be taken into account that sequencing of the 16S rRNA gene and biochemical tests are useful for the identification of several species, but it is necessary to incorporate other genes (hsp 65 and rpo B) to obtain accurate identification.